Ventricular Geometry in Post-Myocardial Infarction Aneurysms Implications for Surgical Ventricular Restoration - Adhyapak, Srilakshmi; Adhyapak, Srilakshmi M. (Springer London : Imprint: Springer, 2012)
Following a transmural myocardial infarctions (MI), the resultant dilated, aneurismal  ventricle can make patient management difficult in those ineligible for cardiac transplantation. This mechanical complication leads to refractory heart failure and continues to be  a persisting  problem for clinical management in both the developed and developing countries of the world. It continues to exist despite improvements in door to needle time for primary coronary interventions. There has been increased interest in potential surgical techniques involved in the palliation of ventricular pathology post-MI. The process of cardiac remodeling has been studied extensively, and recent surgical techniques for ventricular restoration have proven late adverse remodeling. Surgical techniques for  ventricular restoration of these adversely remodeled ventricles aimed at restoring a near normal ventricular geometry consequently have a continuing role in the management of this difficult subset of patients. Ventricular Geometry in Post-Myocardial Infarction Aneurysms: Implications for Surgical Ventricular Restoration provides cardiac surgeons and cardiologists  a definitive perspective of optimal surgical ventricular restoration in patients with advanced heart failure due to large ventricular aneurysms following transmural myocardial infarctions. The authors review  normal and abnormal cardiac anatomy following post myocardial infarction and physiology, with focus on the evolution of surgical techniques aimed  at establishing  an ellipsoid ventricular shape, resulting in near-normal physiological hemodynamics evident at long term.